Spin cat states in ferromagnetic insulators - Sharma, Sanchar; Bittencourt, Victor A.S.V.; Karenowska, Alexy D.; Viola Kusminskiy, Silvia (Physical Review B, 2021)
Generating nonclassical states in macroscopic systems is a long-standing challenge. A promising platform in the context of this quest are novel hybrid systems based on magnetic dielectrics, where photons can couple strongly and coherently to magnetic excitations, although a nonclassical state therein is yet to be observed. We propose a scheme to generate a magnetization cat state, i.e., a quantum superposition of two distinct magnetization directions, using a conventional setup of a macroscopic ferromagnet in a microwave cavity. Our scheme uses the ground state of an ellipsoid shaped magnet, which displays anisotropic quantum fluctuations akin to a squeezed vacuum. The magnetization collapses to a cat state by either a single photon or a parity measurement of the microwave cavity state. We find that a cat state with two components separated by ∼5ℏ is feasible and briefly discuss potential experimental setups that can achieve it.
CRIS-Team Scopus Importer:2021-04-02